The Pending Agenda of the Electricity Sector - Dammert Lira, Alfredo (2015)
This article discusses the structure of the electricity supply. This system mainly consists of three subsystems: the generation, transmission and distribution of electricity. Each system is comprised of different features like its regulation. Given the above, the author tells us the Peruvian case, on the body called the Committee of Economic Operation of the System (COES).